Expanding horizons of cancer immunotherapy: hopes and hurdles - Sonar, Priyanka Vijay; Singh, Anuj Kumar; Mandadi, Sravan; Sharma, Nilesh Kumar (Frontiers in Oncology, 2025)
BackgroundTumor displays various forms of tumor heterogeneity including immune heterogeneity that allow cancer cells to survive during conventional anticancer drug interventions. Thus, there is a strong rationale for overcoming anticancer drug resistance by employing the components of immune cells. Using the immune system to target tumor cells has revolutionized treatment. Recently, significant progress has been achieved at preclinical and clinical levels to benefit cancer patients.ApproachA review of literature from the past ten years across PubMed, Scopus, and Web of Science focused on immunotherapy strategies. These include immune checkpoint inhibitors (ICIs), tumor-infiltrating lymphocyte therapy, antibody-drug conjugates (ADCs), cancer vaccines, CAR T-cell therapy, and the role of the gut microbiome.ConclusionWhile immunotherapy outcomes have improved, particularly for tumor types such as melanoma and non-small cell lung cancer (NSCLC), challenges persist regarding predictive biomarker identification and better management. Ongoing research on modifiers of immune function like gut microbiome-derived metabolites, next-generation ADCs, and new classes of biologics is warranted. Overall, continued investigation toward optimizing synergistic immunotherapeutic combinations through strategic drug delivery systems is imperative for preclinical and clinical success in cancer patients.